2018
DOI: 10.1002/smll.201802524
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization‐Induced Emission Enhancement of a Deep‐Blue Luminescence Material with Tunable Mechano‐ and Thermochromism

Abstract: Organic luminescent materials with the ability to reversibly switch the luminescence when subjected to external stimuli have attracted considerable interest in recent years. However, the examples of luminescent materials that exhibit multiresponsive properties are rarely reported. In this work, a new stimuli‐responsive dye P1 is designed and synthesized with two identical chromophores of naphthalimide, one at each side of an amidoamine‐based spacer. This amide‐rich molecule offers many possibilities for formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Luminescent materials such as phosphors are the substances that emit light in the electromagnetic waves (EM) spectrum after the conversion of the absorbed energy from an energy source. These materials may be classified according to the wide range of excitation energy sources and excitation trigger [2][3][4]. Essentially, photoluminescence is a phenomenon where the emission of light happens when stimulated by short-wavelength light, usually ultraviolet (UV) light or visible light [5].…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent materials such as phosphors are the substances that emit light in the electromagnetic waves (EM) spectrum after the conversion of the absorbed energy from an energy source. These materials may be classified according to the wide range of excitation energy sources and excitation trigger [2][3][4]. Essentially, photoluminescence is a phenomenon where the emission of light happens when stimulated by short-wavelength light, usually ultraviolet (UV) light or visible light [5].…”
Section: Introductionmentioning
confidence: 99%
“…[ 75 ] Therefore, a myriad of AIEgens with diverse stimuli‐responsive properties has been developed in recent years, and the resulting materials have shown broad application prospects. [ 76–96 ]…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that 1,8‐naphthalimide hydrazone‐conjugated organic compounds with planar structures and an electron‐donating group, are able to increase fluorescence quantum yields and tune the emission wavelength to longer regions [9] . Stimuli‐responsive dyes with two naphthalimide chromophores have been reported, and offer a good many of intra‐ and intermolecular hydrogen bond interactions and exhibit an apparent mechanochromic fluorescent behavior, which is extremely rare among naphthalimide‐based molecules in the solid state [10] . Previous work has shown that mechanical forces can induce the morphology change through enhancing π‐π stacking and destroying hydrogen bonds and twisted molecular conformation and the absence of intermolecular interaction lead to a loose packing mode, [11] and the transformation of molecular packing accounts for the obvious mechanofluorochromic effect [12] …”
Section: Introductionmentioning
confidence: 99%